(untitled) (Lex localis - Journal of Local Self-Government, 2025)
In the digital age, social media advertising has emerged as a primary driver of business visibility, customer engagement, and overall growth. With English being the global lingua franca, proficiency in the language plays a critical role in shaping the effectiveness of social media advertising campaigns. This paper examines how English language proficiency influences message clarity, audience engagement, consumer trust, and cross-cultural communication in digital marketing spaces. It explores the importance of grammar, vocabulary, tone, and stylistic choices in crafting persuasive advertisements, alongside the use of English as a unifying medium for global markets. Additionally, it investigates challenges faced by businesses in non-English speaking regions and how limited proficiency can hinder advertising effectiveness. The research also emphasizes strategies such as content localization, bilingual campaigns, and professional training to overcome language barriers. Drawing on studies from linguistics, marketing, and business communication, this paper argues that English proficiency is not merely a linguistic asset but a strategic business tool for enhancing social media advertising and driving sustainable growth. The findings suggest that businesses investing in language skills alongside digital marketing strategies are better positioned to compete in globalized markets.